Fennel (Foeniculum vulgare Miller) for the management of menopausal women's health: A systematic review and meta-analysis. (May 2021) - Lee, Hye Won; Ang, Lin; Kim, Eunseop; Lee, Myeong Soo
Abstract: This review aimed to evaluate the current evidence on the effectiveness and safety of fennel ( Foeniculum vulgare Miller) for managing menopausal women's health. Fourteen databases were searched. We included randomized controlled trials (RCTs) that evaluated any type of fennel treatment in menopausal women. Seven RCTs that met our inclusion criteria were identified and analyzed. The included RCTs had concerning risks of bias in general. Two RCTs compared the effects of fennel with placebo, and the meta-analysis results favored fennel for improving menopausal symptoms (n = 145, standard mean difference −1.32 [-1.76, −0.87], p < 0.00001). Other studies failed to show beneficial effects of fennel in terms of sexual function, quality of life (QoL), and psychological health. No serious adverse events were reported. Our review presented evidence for fennel improving menopausal symptoms. However, the effectiveness and safety of fennel in improving QoL, and psychological health remains unclear. Highlights: Several trials reported that the effects of fennel for managing menopausal symptoms, including hot flushes, and vaginal atrophy, were favorable. Seven randomized clinical trials met our inclusion criteria, and most of them had concerning risk of bias. Our review suggested the effectiveness for fennel improving menopausal symptoms but unclear for improving QoL, and psychological health.